Effectiveness of an oral cholera vaccine campaign to prevent clinically-significant cholera in Odisha State, India. Issue 21 (15th May 2015) - Wierzba, Thomas F.; Kar, Shantanu K.; Mogasale, Vijayalaxmi V.; Kerketta, Anna S.; You, Young Ae; Baral, Prameela; Khuntia, Hemant K.; Ali, Mohammad; Kim, Yang Hee; Rath, Shyam Bandhu; Bhattachan, Anuj; Sah, Binod
Highlights A phase III, clinical trial conducted in Kolkata showed that Shanchol, an oral cholera vaccine, provides 65% protection against cholera over five years. To test the usefulness of this vaccine when deployed by public health department personnel using local resources, we conducted a mass vaccination campaign in a rural cholera-endemic area of India. At the end of two years, the vaccine was found to reduce cholera cases by 69%. This study supports widespread use of Shanchol by local health departments in cholera-affected areas of India and other nations.